Development and usability of a computer‐tailored pedometer‐based physical activity advice for breast cancer survivors. (11th August 2014) - De Cocker, K.; Charlier, C.; Van Hoof, E.; Pauwels, E.; Lechner, L.; Bourgois, J.; Spittaels, H.; Vandelanotte, C.; De Bourdeaudhuij, I.
<x xml:space="preserve">Abstract</x> This observational study aimed to adapt a computer‐tailored step advice for the general population into a feasible advice for breast cancer survivors and to test its usability. First, several adaptations were made to the original design (adding cancer‐related physical activity (PA) barriers and beliefs, and self‐management strategies to improve survivors' personal control). Second, the adapted advice was evaluated in two phases: (1) a usability testing in healthy women (n = 3) and survivors (n = 6); and (2) a process evaluation during 3 weeks in breast cancer survivors (n = 8). Preliminary usability testing revealed no problems during logging‐in; however, three survivors misinterpreted some questions. After refining the questionnaire and advice, survivors evaluated the advice as interesting, attractive to read, comprehensible and credible. Inactive survivors found the advice novel, but too long. The process evaluation indicated that the majority of the women (n = 5/8) reported increased steps. Monitoring step counts by using a pedometer was perceived as an important motivator to be more active. To conclude, this study provides initial support for the usability and acceptability of a computer‐tailored pedometer‐based PA advice for breast cancer survivors. After testing efficacy and effectiveness of this intervention, this tool can broaden the reach of PA promotion in breast cancer survivors.